METODE TRANSFORMASI PENGETAHUAN TERHADAP PENINGKATAN KOMPETENSI (PELATIHAN KOMPUTER) SMP, SMA, DAN UMUM DI DESA BUKIT LANGKAP KEC. KARANG JAYA KAB.MUSI RAWAS UTARA - Suyadi Suyadi; Irma Idayati; Achmad Feri Ariansyah (Jurnal Media Ekonomi (JURMEK), 2019)
The impact of the expandingeconomy cause the decrease community incomesespecially the income of farmer income, from the price of rubber, palm oil, crops which were getting lower in price. The growing need for life requires the community to be able to fulfill their daily needs even with minimum fulfillment. Our concern for the future generation of children will inspire us to conduct direct observations of people in Bukit Langkap village kec Karang Jaya Kab. Musi Jaya Kab. Rawas Utara. The goal is to produce Knowledge Transformation Method is by training approach to improve children competency in junior high schooland general education in Bukit Langkap Village. Identifyingthe needs sueh asthe edulpment which use in training we get it by rent. The main target is senior and junior high sehool students the study principle by direct seminars with a practical approcch from the training result will be done a produce knowledge transform method by trahing /practice approach in using computer comprehension such as hase introduce of computer, can programe the word, exsel, and powerpoin, and we hope will estabiish the sustainability relationship even thoug the research has beeb completed.